Governance Practices and Leadership Styles as Determinants of Institutional Performance in Colleges of Education in the Volta Region of Ghana - Abudetse, Richard Kwaku; Vinyo, Innocent Yao; Ayetor, Samuel Edem (Journal of Education and Practice, 2025)
Purpose: This study examines the relationship between governance practices, leadership styles and institutional performance in Colleges of Education in the Volta Region of Ghana. With their transition into degree-conferring institutions, the need for effective governance and leadership is imperative. The study was grounded in Agency Theory and Transformational Leadership Theory. Methodology: A quantitative cross-sectional explanatory design was employed. Data were collected from 120 respondents, including principals, registrars, council members, and senior lecturers, through a structured questionnaire. Respondents were selected through purposive and stratified sampling to ensure stakeholder representation. The data were analyzed using descriptive statistics, correlation, and multiple regression with SPSS. Reliability was tested using Cronbach’s alpha, and diagnostic checks were conducted to validate the model. Findings: Governance practices, particularly council oversight, financial transparency, and compliance with regulatory standards, strongly influenced institutional outcomes such as accreditation, staff development, and student success. Leadership styles also mattered: transformational and participatory leadership enhanced innovation and adaptability, whereas transactional and authoritarian leadership were linked to ineffective outcomes. The study demonstrates governance as a moderator that strengthens the effectiveness of participatory and transformational leadership. Unique Contribution to Theory, Policy and Practice: The study extends theory by integrating Agency and Transformational Leadership frameworks in higher education. Beyond Ghana, its implications apply to teacher education reform in emerging contexts where governance and leadership challenges coexist. Strengthening governance and leadership supports the Colleges’ new mandate and informs education reform policies that emphasize accountability, innovation, and resilience.